Assessing the impact of clinical pharmacy services on the healthcare outcomes of patients attending an outpatient haemodialysis unit in a rural hospital in Egypt: a quasi-experimental study - Nagib, Reem; Abdul-Latif, Maha; Sakoury, Hoda S.; Elrggal, Mahmoud E.; Cheema, Ejaz; Elnaem, Mohamed Hassan Abdelaziz; El-Fass, Karim A. (Oxford University Press, 2021)
Objectives This study aimed to investigate the impact of newly introduced clinical pharmacy services on the health care of chronic haemodialysis patients attending an outpatient haemodialysis unit in a rural hospital with limited resources in Alexandria, Egypt. Methods A quasi-experimental pre-/post-test study was conducted from November 2016 till June 2018. Clinical pharmacists collected relevant information using a pre-specified form. Patients’ data were reviewed for drug-related problems (DRPs), which were documented using the Pharmaceutical Care Network Europe (PCNE) classification system, version 8.02 and resolved by the clinical pharmacists. Measured values of calcium, phosphorus and haemoglobin were compared with target levels set by the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. Proportions of patients achieving therapeutic values of each parameter were compared before and after implementing the program using the McNemar test. We also reported the analysis of DRPs identified and addressed by the clinical pharmacy team. Key findings A total of 685 DRPs were identified during the follow-up period. Improper dose and inappropriate drug selection were the most common DRPs (45.8% and 18.9%, respectively). There was a statistically significant increase in the proportion of patients achieving target corrected calcium levels (30% pre-intervention versus 69.6% post-intervention, P = 0.001) and haemoglobin levels (9.1% pre-intervention versus 31.9% post-intervention, P = 0.003), but not in phosphorus levels (18.6% pre-intervention versus 22% post-intervention, P = 0.7). Conclusions Clinical pharmacists were able to resolve frequent DRPs and improve some markers of health care in haemodialysis patients.